Searching for Roth, Kafka, and the Other Europe in Spain - Bryla, Martyna Marika (Purdue University Press, 2023)
This essay explores the connections between Philip Roth, Franz Kafka, and the conceptual category of "the Other Europe" through the lens of personal experience and academic inquiry. By retracing Roth’s engagement with East-Central Europe, it reflects on the geopolitical and cultural dimensions of the region, emphasizing its liminal identity as both marginal and central to the Western imagination. Focusing on Roth’s The Professor of Desire and The Prague Orgy, the essay analyzes the significance of Roth’s East-Central European experience for his narrative and thematic sensibility, highlighting the formative roles of Kafka, Kundera, and Schulz in Roth’s writing. In turn, Roth’s interest in the literary cultures of East-Central Europe is presented as pivotal to the author’s own academic journey and the process of reconciling her Polish cultural background with her life in Spain, underscoring the transformative power of literature in transcending borders and fostering intercultural connections.
Cuento con el permiso de Purdue University Press para depositar el artículo en RIUMA. Adjunto la comunicación con la editorial. Dear Martyna, Yes, you may deposit in your institutional repository. Best, Becki Corbin Administrative Assistant Purdue University Press 765-494-2038 -----Original Message----- From: martynabryla <martynabryla@uma.es> Sent: Monday, January 20, 2025 3:51 AM To: Purdue Press <pupress@purdue.edu> Subject: Re: permission to deposit my article in an institutional repository Dear Becki, I would like to reiterate my request to deposit my article published in Philip Roth Studies in my University's institutional repository under Creative Commons licence (https://riuma.uma.es/xmlui/). The title of the article is "Searching for Roth, Kafka, and the Other Europe in Spain." Thank you. Kind regards, Martyna Bryla
Keywords: Kafka, Franz (1883-1924) - Crítica e interpretación; Roth, Philip - Crítica e interpretación; Philip Roth; Eastern Europe; The Other Europe; Central Europe; Milan Kundera; Franz Kafka; Bruno Schulz